Fraud in legal entities? Structural challenges in Ecuadorian criminal law - León González, Pablo Andrés (2025)
This article critically examines the criminal liability of legal entities under Ecuadorian law, with particular emphasis on the attribution of intent (dolo). It acknowledges that the Ecuadorian Criminal Code has institutionalized this form of liability, yet fails to provide sufficient dogmatic tools to address the subjective elements of crime within corporate entities. Through a normative, jurisprudential, and theoretical analysis, the article argues that directly transposing the concept of intent from natural persons to legal entities is unsatisfactory both conceptually and functionally. To address this gap, it proposes an epistemological reconstruction of corporate dolo based on systemic functionalism, shifting the focus from individual will to the organizational structures that condition the avoidability of the offense. The study concludes that a model of self-responsibility, coupled with a notion of structural dolo, allows for a more coherent and legitimate form of attribution—avoiding both vicarious automatism and outright denial of responsibility. This proposal opens an alternative path for rethinking criminal law theory in the corporate context in Ecuador and calls for a critical reassessment of classical conceptual frameworks in light of the complexity of collective subjects.